VILMOS GAZDAG: THE EFFECT OF MILITARY SERVICE ON THE LANGUAGE USE OF HUNGARIAN MEN IN TRANSCARPATHIA - GAZDAG, VILMOS (Linguistic Bulletin (Movoznavchyi Visnyk), 2021)
Summary. Introduction. In connection with the Hungarian military language in Transcarpathia, the peculiar situation arose that it did not function as a professional language or as a group language in the traditional sense. This is related to the fact that official communication in the military only occurs in the current state language. Accordingly, men living in Transcarpathia learned the military language in Russian or Ukrainian, depending on the length of their military service (i.e., whether they served before or after 1991). Additionally, precisely due to the lack of opportunities to use the mother tongue, it is impossible to speak of Hungarian military slang in the case of military service. Purpose. In the present paper, we attempt to present the lexical borrowings from the state language established in connection with military life in the language use of Hungarian men in Transcarpathia. The work is based on the results of an empirical study paying special attention to informants' changes in language skills. Results. Due to the limitations of the pandemic, we conducted our study in the form of an online survey. We published a link to the questionnaire on the social network Facebook in early December 2020, and as of January 27, 2021, when work began on this article, the questionnaire was completed and sent by 25 people. Eight people served in the army in independent Ukraine, and the remaining 17 people were still in the Soviet Army. The questionnaires contained mainly questions related to military service, comrades-in-arms, military units, means, equipment, clothing, and food used in the army. The purpose of such questions is for respondents to spontaneously, rather than through direct questions, recall borrowings known to them that originate from the state language. We tried to summarize the obtained answers briefly, emphasizing separately the Russian and Ukrainian elements mentioned by the respondents. In the course of the research we managed to identify such borrowings from the state languages, which had not been fixed at the scientific level before. The results also revealed the existence of such a phenomenon as the polyvariance of borrowings or the parallel use of Russian and Ukrainian equivalents. Conclusion. After demobilization, military terms that appear in the memories of former conscripts, due to lack of knowledge of their counterparts in their native language, are replaced by Slavic elements learned during the service, which are naturally assimilated in the Transcarpathian Hungarian dialects.